Comparison of dental caries cases in paediatric and adult patients at the Dental Clinic of the Baturiti II Community Health Centre, Tabanan: Perbandingan kasus karies gigi pada pasien anak dengan dewasa di Poli Gigi UPTD Puskesmas Baturiti II Tabanan - Dewi, Ni Made Yunita Maharani; Idaryati, Ni Putu; Ariani, Ni Luh Putu (Makassar Dental Journal, 2025)
Oral health plays an important role in creating a healthy lifestyle. Caries are the most common oral disease, affecting 60-90% of school children and nearly 100% of adults. The purpose of this study was to determine the comparison of dental caries cases in paediatric and adult patients at the Baturiti II Tabanan Community Health Centre dental clinic. This quantitative study with a des-criptive observational design was conducted using purposive sampling on paediatric patients aged 6-11 years and adult patients aged 26-45 years who had dental caries at the Baturiti II Tabanan Community Health Centre Dental Clinic. The results of this study showed that there were 22 patients with dental caries who visited the clinic from January to March 2025. The highest caries group based on age was adults (82.4%), while based on gender, there were 12 males (54.5%). It was concluded that education is needed on how to maintain dental and oral health, as well as how to prevent, treat, and manage caries appropriately, in order to reduce the incidence of caries in both children and adults.